Zenab’sprotective scroll: A migrant voice, and a graphic essay - Ramos, M. J. (Border crossings in and out of Europe, 2022)
Despite its epistemological shortcomings, the anthropological use of qualitative methods and of argumentation by illustration as a source of knowledge has a positive side: that of helping us surmounting the opposition between us and the others and allow for empathy to check our analytical and cultural biases. Availability to listen and to let other people’s minds in ours is an essential corollary of anthropological research. The following paragraphs and drawings are an attempt to both let a “migrant voice” be freely expressed within an academic publication and a mediated form of reaching out to cultural values and experiences that lay outside the bounds of the host population. It offers an edited and anonymised testimony interspersed with drawings inspired by the Ethiopian art of the abǝnnät.